2015
DOI: 10.3892/ijmm.2015.2330
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of RANKL-induced osteoclastogenesis through the suppression of the ERK signaling pathway by astragaloside IV and attenuation of titanium-particle-induced osteolysis

Abstract: Astragaloside IV (AS-IV) is a natural plant extract that enhances osteoblast activity, and therefore, has the potential to treat osteoclast‑related diseases. Such diseases include osteoporosis, periodontal disease, rheumatoid arthritis and aseptic prosthesis loosening. However, data associating the effects of AS‑IV on osteoclasts are limited. The aim of the present study was to assess the effect of AS‑IV on osteoclasts in vitro and in vivo. The in vitro studies demonstrated that AS‑IV exerts potent inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 52 publications
1
24
1
Order By: Relevance
“…It was found that the mRNA expression level of osteoclast-related genes decreased following the treatment with DAPT. Several previous studies reported that RANKLinduced ERK, and JNK pathway played a crucial role in the formation of osteoclast (Li et al, 2015;Liu et al, 2014), but few studies discussed the Notch signaling pathway. Notch signaling is highly conserved, and it plays an essential role in varieties of cell processes.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the mRNA expression level of osteoclast-related genes decreased following the treatment with DAPT. Several previous studies reported that RANKLinduced ERK, and JNK pathway played a crucial role in the formation of osteoclast (Li et al, 2015;Liu et al, 2014), but few studies discussed the Notch signaling pathway. Notch signaling is highly conserved, and it plays an essential role in varieties of cell processes.…”
Section: Discussionmentioning
confidence: 99%
“…ERK signaling pathway has been implicated in the protective effects of AS-IV in different models. AS-IV exerted potent inhibitory effects on receptor activator for nuclear factor-κB ligand (RANKL)-induced osteoclastogenesis by suppressing ERK signaling pathway in vitro [31]. AS-IV also prevented glutamate-induced apoptosis in PC12 neuroblastic cells by blocking the phosphorylation of ERK [32].…”
Section: Discussionmentioning
confidence: 99%
“…During bacterial infection or trauma, dental pulp odontoblasts proliferate and differentiate to form a reparative dentine that prevents lesions . AS‐IV has been reported to affect RANKL‐induced osteoclastogenesis, and RANKL signaling is related to odontoblastic differentiation . However, whether AS‐IV participates in odontoblastic differentiation of dental pulp cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its extensive pharmacological activities, including anti‐inflammatory, antioxidant, antitumor, and immunomodulatory effects, AS‐IV has been found to regulate a variety of pathophysiological processes . AS‐IV reportedly affects receptor activator of nuclear factor‐κB (RANKL)‐induced osteoclastogenesis and titanium particle‐induced osteolysis, suggesting that AS‐IV is a potential agent for the treatment of osteoclast‐related diseases . Intriguingly, RANKL signaling also helps to regulate odontoblast differentiation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation